Les romans du Graal et le culte du Précieux Sang - Edina Bozoky (Tabularia)
Several themes in Grail literature reflect the devotion to the Passion of Christ, and especially to the Holy Blood. After outlining the development of French Grail romances (late 12th to 13th centuries) this paper will set out the ways in which the Grail and the Bleeding Lance came to be identified with relics from the Passion of Christ (the Grail as a dish from the Last Supper in which Joseph of Arimathea received Christ's blood; the Bleeding Lance as the lance with which Longinus pierced Christ’s side). Finally, visions of the Grail will be presented as the enactment of the dogma of transubstantiation, which is closely linked to the religious significance of the Blood of Christ.